Glaze for hot-bending formed rock plate with antibacterial effect and preparation method of glaze
By using kaolin, nano zinc oxide and other materials in the glaze for hot-bending rock slabs, and improving the activity of raw materials through modification treatment, the problems of poor antibacterial properties and insufficient acid and corrosion resistance of existing glazes have been solved, and the long-lasting antibacterial, anti-fouling and acid and corrosion resistance of glazes have been significantly improved.
Patent Information
- Application Number
- CN202411847668.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-15
AI Technical Summary
The existing glazes for hot-bending rock slabs have poor antibacterial properties, are not long-lasting in antibacterial properties, and are also poor in soil resistance. The product has insufficient acid and corrosion resistance, which limits the efficiency of the product.
Kaolin, nano zinc oxide, potassium feldspar, sodium feldspar, ultra-white sand combined with bentonite, and modified wollastonite and modified talc are added. The active performance of the raw materials is optimized through proton irradiation and modification liquid to form a glaze with long-lasting antibacterial and antifouling properties.
It significantly improves the antibacterial properties of glazes and the durability and stain resistance, while enhancing the acid and corrosion resistance of the product, improving the overall performance of the product.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glazes for rock slabs, and in particular to a glaze for hot-bending rock slabs with antibacterial effect and a preparation method thereof. Background Art
[0002] Usually wash basins and dish basins are made of acrylic, but acrylic is a resin and cannot be made into one piece. It is not resistant to high temperatures, acids and alkalis, and cannot be made into customized patterns. If you use rock slabs as the basic material, it is easy to crack and become brittle during the secondary hot bending and cannot be formed.
[0003] The existing glazes used in hot-bent rock panels have poor antibacterial properties, are not durable, and have poor antifouling properties. It is difficult to coordinate and improve the antifouling and antibacterial durability, and the product's acid and corrosion resistance is poor, which limits the product's use efficiency. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a glaze for hot-bent rock slabs with antibacterial effect and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a glaze for hot-bending rock panels with antibacterial effect, comprising the following raw materials in parts by weight: 35-40 parts of kaolin, 10-15 parts of modified wollastonite, 8-12 parts of nano zinc oxide, 5-8 parts of potassium feldspar, 5-8 parts of sodium feldspar, 5-8 parts of super white sand, 4-7 parts of bentonite and 4-7 parts of modified talc.
[0006] Preferably, the preparation method of the modified wollastonite is: S01: irradiate the wollastonite in a proton irradiation box for 10-15 minutes with an irradiation power of 350-400W. After the irradiation is completed, preheat the wollastonite at 60-65°C for 1 hour to obtain a preheated wollastonite body; S02: Add 1-3 parts of silane coupling agent KH550, 2-5 parts of sodium silicate solution and 3-6 parts of nano-alumina agent to 5-8 parts of yttrium nitrate solution, and stir thoroughly to obtain a modified solution; S03: The preheated wollastonite is immersed in a sufficient amount of the modified liquid and stirred. After the stirring is completed, the wollastonite is filtered and dried to obtain the modified wollastonite.
[0007] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the yttrium nitrate solution is 4-7%.
[0008] Preferably, the stirring speed of the stirring treatment is 350-400 r / min, and the stirring time is 1 hour.
[0009] Preferably, the preparation method of the nano alumina agent is: 5-8 parts of nano-alumina, 1-3 parts of sodium alginate solution, 2-5 parts of hydroxyapatite and 4-7 parts of lanthanum chloride solution are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain a nano-alumina agent.
[0010] Preferably, the mass fraction of the sodium alginate solution is 4-6%; the mass fraction of the lanthanum chloride solution is 2-5%.
[0011] Preferably, the preparation method of the modified talc is: S11: Stir flaky talc powder in a sufficient amount of potassium permanganate solution, then wash, filter and dry; S12: 4-7 parts of dry flaky talc, 2-3 parts of nano-silica sol, 1-3 parts of carboxymethyl cellulose, 1-2 parts of nano-calcium carbonate and 5-8 parts of sodium dodecylbenzene sulfonate solution are mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min. After the ball-milling is completed, the mixture is filtered and dried to obtain modified talc.
[0012] Preferably, the mass fraction of the potassium permanganate solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 4-6%.
[0013] The present invention also provides a method for preparing a glaze for hot-bending rock panels having an antibacterial effect, comprising the following steps: Kaolin, modified wollastonite, nano zinc oxide, potassium feldspar, sodium feldspar, ultra-white sand, bentonite and modified talc are wet-milled to obtain a glaze, which is applied to the green body plate at an application rate of 500 g / m 2 Then sinter at 1300℃ for 2h.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The glaze for hot-bending rock slabs of the present invention adopts kaolin, nano zinc oxide, potassium feldspar, sodium feldspar, super white sand and bentonite, and the modified wollastonite and modified talc added are blended with each other and work together, the product has excellent antibacterial performance and durability, and the antifouling and antibacterial properties of the product can be coordinated and improved, and the acid corrosion stability of the product is remarkable; the modified wollastonite is subjected to proton irradiation to optimize its active efficiency, and then improved by a modified liquid, and the nano alumina in the modified liquid is improved and then combined with a silane coupling agent KH550 and a sodium silicate solution, and the raw materials are blended and coordinated, and the added nano alumina agent adopts nano alumina to be improved by hydroxyapatite, and the obtained nano alumina agent is coordinated with wollastonite, so as to strengthen the system performance, and the performance of the product is further improved; the modified talc is improved by using flaky talc through specific raw materials, so that the modified talc obtained by coordinating with the modified wollastonite has a better effect, and the performance of the product is further improved. DETAILED DESCRIPTION
[0015] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] The glaze for hot-bending rock panels with antibacterial effect of this embodiment includes the following raw materials in parts by weight: 35-40 parts of kaolin, 10-15 parts of modified wollastonite, 8-12 parts of nano zinc oxide, 5-8 parts of potassium feldspar, 5-8 parts of sodium feldspar, 5-8 parts of super white sand, 4-7 parts of bentonite and 4-7 parts of modified talc.
[0017] The preparation method of the modified wollastonite of this embodiment is: S01: irradiate the wollastonite in a proton irradiation box for 10-15 minutes with an irradiation power of 350-400W. After the irradiation is completed, preheat the wollastonite at 60-65°C for 1 hour to obtain a preheated wollastonite body; S02: Add 1-3 parts of silane coupling agent KH550, 2-5 parts of sodium silicate solution and 3-6 parts of nano-alumina agent to 5-8 parts of yttrium nitrate solution, and stir thoroughly to obtain a modified solution; S03: The preheated wollastonite is immersed in a sufficient amount of the modified liquid and stirred. After the stirring is completed, the wollastonite is filtered and dried to obtain the modified wollastonite.
[0018] The mass fraction of the sodium silicate solution in this embodiment is 2-5%; the mass fraction of the yttrium nitrate solution is 4-7%.
[0019] The stirring speed of the stirring treatment in this embodiment is 350-400 r / min, and the stirring is for 1 hour.
[0020] The preparation method of the nano alumina agent of this embodiment is: 5-8 parts of nano-alumina, 1-3 parts of sodium alginate solution, 2-5 parts of hydroxyapatite and 4-7 parts of lanthanum chloride solution are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain a nano-alumina agent.
[0021] The mass fraction of the sodium alginate solution in this embodiment is 4-6%; the mass fraction of the lanthanum chloride solution is 2-5%.
[0022] The preparation method of the modified talc of this embodiment is: S11: Stir flaky talc powder in a sufficient amount of potassium permanganate solution, then wash, filter and dry; S12: 4-7 parts of dry flaky talc, 2-3 parts of nano-silica sol, 1-3 parts of carboxymethyl cellulose, 1-2 parts of nano-calcium carbonate and 5-8 parts of sodium dodecylbenzene sulfonate solution are mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min. After the ball-milling is completed, the mixture is filtered and dried to obtain modified talc.
[0023] The mass fraction of the potassium permanganate solution in this embodiment is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 4-6%.
[0024] A method for preparing a glaze for hot-bending rock panels with antibacterial effect in this embodiment includes the following steps: Kaolin, modified wollastonite, nano zinc oxide, potassium feldspar, sodium feldspar, ultra-white sand, bentonite and modified talc are wet-milled to obtain a glaze, which is applied to the green body plate at an application rate of 500 g / m 2 Then sinter at 1300℃ for 2h.
[0025] Example 1. The glaze for hot-bending rock panels with antibacterial effect of this embodiment includes the following raw materials in parts by weight: 35 parts of kaolin, 10 parts of modified wollastonite, 8 parts of nano zinc oxide, 5 parts of potassium feldspar, 5 parts of sodium feldspar, 5 parts of super white sand, 4 parts of bentonite and 4 parts of modified talc.
[0026] The preparation method of the modified wollastonite of this embodiment is: S01: irradiate the wollastonite in a proton irradiation box for 10 minutes at an irradiation power of 350W. After the irradiation is completed, preheat the wollastonite at 60°C for 1 hour to obtain a preheated wollastonite body; S02: Add 1 part of silane coupling agent KH550, 2 parts of sodium silicate solution and 3 parts of nano-alumina agent to 5 parts of yttrium nitrate solution, and stir thoroughly to obtain a modified solution; S03: The preheated wollastonite is immersed in a sufficient amount of the modified liquid and stirred. After the stirring is completed, the wollastonite is filtered and dried to obtain the modified wollastonite.
[0027] The mass fraction of the sodium silicate solution in this embodiment is 2%; the mass fraction of the yttrium nitrate solution is 4%.
[0028] The stirring speed of the stirring process in this embodiment is 3500 r / min, and the stirring is performed for 1 hour.
[0029] The preparation method of the nano alumina agent of this embodiment is: 5 parts of nano-alumina, 1 part of sodium alginate solution, 2 parts of hydroxyapatite and 4 parts of lanthanum chloride solution were mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling was completed, the mixture was filtered and dried to obtain a nano-alumina agent.
[0030] The mass fraction of the sodium alginate solution in this embodiment is 4%; the mass fraction of the lanthanum chloride solution is 2%.
[0031] The preparation method of the modified talc of this embodiment is: S11: Stir flaky talc powder in a sufficient amount of potassium permanganate solution, then wash, filter and dry; S12: 4 parts of dry flaky talc, 2 parts of nano-silica sol, 1 part of carboxymethyl cellulose, 1 part of nano-calcium carbonate and 5 parts of sodium dodecylbenzene sulfonate solution are mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min. After the ball-milling is completed, the mixture is filtered and dried to obtain modified talc.
[0032] The mass fraction of the potassium permanganate solution in this embodiment is 2%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 4%.
[0033] A method for preparing a glaze for hot-bending rock panels with antibacterial effect in this embodiment includes the following steps: Kaolin, modified wollastonite, nano zinc oxide, potassium feldspar, sodium feldspar, ultra-white sand, bentonite and modified talc are wet-milled to obtain a glaze, which is applied to the green body plate at an application rate of 500 g / m 2 Then sinter at 1300℃ for 2h.
[0034] Example 2. The glaze for hot-bending rock panels with antibacterial effect of this embodiment includes the following raw materials in parts by weight: 40 parts of kaolin, 15 parts of modified wollastonite, 12 parts of nano zinc oxide, 8 parts of potassium feldspar, 8 parts of sodium feldspar, 8 parts of super white sand, 7 parts of bentonite and 7 parts of modified talc.
[0035] The preparation method of the modified wollastonite of this embodiment is: S01: irradiate the wollastonite in a proton irradiation box for 15 minutes at an irradiation power of 400 W. After the irradiation is completed, preheat the wollastonite at 65° C. for 1 hour to obtain a preheated wollastonite body; S02: Add 3 parts of silane coupling agent KH550, 5 parts of sodium silicate solution and 6 parts of nano-alumina agent to 8 parts of yttrium nitrate solution, and stir thoroughly to obtain a modified solution; S03: The preheated wollastonite is immersed in a sufficient amount of the modified liquid and stirred. After the stirring is completed, the wollastonite is filtered and dried to obtain the modified wollastonite.
[0036] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the yttrium nitrate solution is 7%.
[0037] The stirring speed of the stirring process in this embodiment is 400 r / min, and the stirring is performed for 1 hour.
[0038] The preparation method of the nano alumina agent of this embodiment is: 8 parts of nano-alumina, 3 parts of sodium alginate solution, 5 parts of hydroxyapatite and 7 parts of lanthanum chloride solution were mixed and ball-milled at a speed of 1500 r / min for 2 hours. After the ball-milling was completed, the mixture was filtered and dried to obtain a nano-alumina agent.
[0039] The mass fraction of the sodium alginate solution in this embodiment is 6%; the mass fraction of the lanthanum chloride solution is 5%.
[0040] The preparation method of the modified talc of this embodiment is: S11: Stir flaky talc powder in a sufficient amount of potassium permanganate solution, then wash, filter and dry; S12: 7 parts of dry flaky talc, 3 parts of nano-silica sol, 3 parts of carboxymethyl cellulose, 2 parts of nano-calcium carbonate and 8 parts of sodium dodecylbenzene sulfonate solution are mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min. After the ball-milling is completed, the mixture is filtered and dried to obtain modified talc.
[0041] The mass fraction of the potassium permanganate solution in this embodiment is 5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 6%.
[0042] A method for preparing a glaze for hot-bending rock panels with antibacterial effect in this embodiment includes the following steps: Kaolin, modified wollastonite, nano zinc oxide, potassium feldspar, sodium feldspar, ultra-white sand, bentonite and modified talc are wet-milled to obtain a glaze, which is applied to the green body plate at an application rate of 500 g / m 2 Then sinter at 1300℃ for 2h.
[0043] Example 3. The glaze for hot-bending rock panels with antibacterial effect of this embodiment includes the following raw materials in parts by weight: 37.5 parts of kaolin, 12.5 parts of modified wollastonite, 10 parts of nano zinc oxide, 6.5 parts of potassium feldspar, 6.5 parts of sodium feldspar, 6.5 parts of super white sand, 5.5 parts of bentonite and 5.5 parts of modified talc.
[0044] The preparation method of the modified wollastonite of this embodiment is: S01: irradiate the wollastonite in a proton irradiation box for 12.5 min at an irradiation power of 375 W. After the irradiation is completed, preheat the wollastonite at 62.5° C. for 1 h to obtain a preheated wollastonite body; S02: Add 2 parts of silane coupling agent KH550, 3.5 parts of sodium silicate solution and 4.5 parts of nano-alumina agent to 6.5 parts of yttrium nitrate solution, and stir thoroughly to obtain a modified solution; S03: The preheated wollastonite is immersed in a sufficient amount of the modified liquid and stirred. After the stirring is completed, the wollastonite is filtered and dried to obtain the modified wollastonite.
[0045] The mass fraction of the sodium silicate solution in this embodiment is 3.5%; the mass fraction of the yttrium nitrate solution is 5.5%.
[0046] The stirring speed of the stirring process in this embodiment is 375 r / min, and the stirring is performed for 1 hour.
[0047] The preparation method of the nano alumina agent of this embodiment is: 6.5 parts of nano-alumina, 2 parts of sodium alginate solution, 3.5 parts of hydroxyapatite and 5.5 parts of lanthanum chloride solution were mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling was completed, the mixture was filtered and dried to obtain a nano-alumina agent.
[0048] The mass fraction of the sodium alginate solution in this embodiment is 5%; the mass fraction of the lanthanum chloride solution is 3.5%.
[0049] The preparation method of the modified talc of this embodiment is: S11: Stir flaky talc powder in a sufficient amount of potassium permanganate solution, then wash, filter and dry; S12: 5.5 parts of dry flaky talc, 2.5 parts of nano-silica sol, 2 parts of carboxymethyl cellulose, 1.5 parts of nano-calcium carbonate and 6.5 parts of sodium dodecylbenzene sulfonate solution were mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min. After the ball-milling was completed, the mixture was filtered and dried to obtain modified talc.
[0050] The mass fraction of the potassium permanganate solution in this embodiment is 3.5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 5%.
[0051] A method for preparing a glaze for hot-bending rock panels with antibacterial effect in this embodiment includes the following steps: Kaolin, modified wollastonite, nano zinc oxide, potassium feldspar, sodium feldspar, ultra-white sand, bentonite and modified talc are wet-milled to obtain a glaze, which is applied to the green body plate at an application rate of 500 g / m 2 Then sinter at 1300℃ for 2h.
[0052] Comparative Example 1. The difference from Example 3 is that no modified wollastonite is added.
[0053] Comparative Example 2. The difference from Example 3 is that no modifying liquid is added to the modified wollastonite.
[0054] Comparative Example 3. The difference from Example 3 is that no nano alumina agent is added to the modified liquid.
[0055] Comparative Example 4. The difference from Example 3 is that the nano alumina agent is replaced by nano alumina.
[0056] Comparative Example 5. The difference from Example 3 is that no modified talc is added.
[0057] Comparative Example 6. The difference from Example 3 is that the modified talc is replaced by talc.
[0058] The product performance tests of Examples 1-3 and Comparative Examples 1-6 are as follows:
[0059] It can be seen from Comparative Examples 1-6 and Example 3 that the product of Example 3 has excellent antibacterial durability and antifouling performance, and the acid resistance and stability of the product are remarkable; The present invention does not add modified wollastonite or modified talc, and the performance of the product deteriorates significantly. The two are used in coordination and synergy, and the product performance effect is most significant. In addition, no modifying liquid is added to the modified wollastonite, no nano-alumina agent is added to the modifying liquid, the nano-alumina agent is replaced by nano-alumina, and the modified talc is replaced by talc. The product raw material obtained by the specific method of the present invention has the most significant product performance effect. The effects of other methods are not as obvious as those of the present invention.
[0060] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0061] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A glaze for hot-bending rock panels with antibacterial properties, characterized in that: It includes the following raw materials in parts by weight: 35-40 parts of kaolin, 10-15 parts of modified wollastonite, 8-12 parts of nano zinc oxide, 5-8 parts of potassium feldspar, 5-8 parts of sodium feldspar, 5-8 parts of super white sand, 4-7 parts of bentonite and 4-7 parts of modified talc.
2. The glaze for hot-bending rock panels with antibacterial effect according to claim 1, characterized in that: The preparation method of the modified wollastonite is: S01: irradiate the wollastonite in a proton irradiation box for 10-15 minutes with an irradiation power of 350-400W. After the irradiation, preheat the wollastonite at 60-65°C for 1 hour to obtain a preheated wollastonite body; S02: Add 1-3 parts of silane coupling agent KH550, 2-5 parts of sodium silicate solution and 3-6 parts of nano-alumina agent to 5-8 parts of yttrium nitrate solution, and stir thoroughly to obtain a modified solution; S03: The preheated wollastonite is immersed in a sufficient amount of the modified liquid and stirred. After the stirring is completed, the wollastonite is filtered and dried to obtain the modified wollastonite.
3. The glaze for hot-bending rock panels with antibacterial effect according to claim 2, characterized in that: The mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the yttrium nitrate solution is 4-7%.
4. The glaze for hot-bending rock panels with antibacterial effect according to claim 2, characterized in that: The stirring speed of the stirring treatment is 350-400 r / min, and the stirring is for 1 hour.
5. The glaze for hot-bending rock panels with antibacterial effect according to claim 2, characterized in that: The preparation method of the nano alumina agent is: 5-8 parts of nano-alumina, 1-3 parts of sodium alginate solution, 2-5 parts of hydroxyapatite and 4-7 parts of lanthanum chloride solution are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain a nano-alumina agent.
6. The glaze for hot-bending rock panels with antibacterial effect according to claim 5, characterized in that: The mass fraction of the sodium alginate solution is 4-6%; the mass fraction of the lanthanum chloride solution is 2-5%.
7. The glaze for hot-bending rock panels with antibacterial effect according to claim 1, characterized in that: The preparation method of the modified talc is: S11: Stir flaky talc powder in a sufficient amount of potassium permanganate solution, then wash, filter and dry; S12: 4-7 parts of dry flaky talc, 2-3 parts of nano-silica sol, 1-3 parts of carboxymethyl cellulose, 1-2 parts of nano-calcium carbonate and 5-8 parts of sodium dodecylbenzene sulfonate solution are mixed and ball-milled for 2 hours at a ball-milling speed of 1500 r / min. After the ball-milling is completed, the mixture is filtered and dried to obtain modified talc.
8. The glaze for hot-bending rock panels with antibacterial effect according to claim 7, characterized in that: The mass fraction of the potassium permanganate solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 4-6%.
9. A method for preparing a glaze for hot-bending rock panels with antibacterial effect as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: Kaolin, modified wollastonite, nano zinc oxide, potassium feldspar, sodium feldspar, ultra-white sand, bentonite and modified talc are wet-milled to obtain a glaze, which is applied to the green body plate at an application rate of 500 g / m 2 Then sinter at 1300℃ for 2h.